N‐Heterocyclic Carbene Catalyzed [3+2] Cycloaddition of Enals with Masked Cinnamates for the Asymmetric One‐Pot Synthesis of Adipic Acid Derivatives. Issue 53 (22nd August 2017) - Chen, Xiang‐Yu; Li, Sun; Sheng, He; Liu, Qiang; Jafari, Ehsan; von Essen, Carolina; Rissanen, Kari; Enders, Dieter
Abstract: A novel short entry to 3, 4‐disubstituted adipic acids has been developed by employing an asymmetric NHC‐catalyzed [3+2] cycloaddition of enals with masked cinnammates in moderate to good yields and high stereoselectivities. The synthetic utility of the protocol was demonstrated by the basic conversion of the masked cyclopentanone intermediates to 3 S, 4 S ‐disubstituted adipic acid precursors of pharmaceutically important gababutins. Abstract : One‐pot to adipic acids : The NHC‐catalyzed asymmetric [3+2] cycloaddition of enals with masked cinnamates opens a new short entry to adipic acid derivatives in moderate to good yields and high stereoselectivities. The utility of the protocol is showcased by the one‐pot asymmetric synthesis of 3 S, 4 S ‐disubstituted adipic acids, precursors for the synthesis of 3, 4‐disubstituted gababutins, which are used for the treatment of various diseases.